Silica‐Coating of Hematite Nanoparticles Using Reactive Water‐Soluble Polyalkoxysiloxanes. (2nd October 2013) - Doermbach, Karla; Agrawal, Garima; Servos, Mark; Schipmann, Susanne; Thies, Sabrina; Klemradt, Uwe; Pich, Andrij
<x xml:space="preserve">Abstract</x> In this article, we report on a new one‐step synthetic route to obtain multi‐functional silica‐coated hematite particles using a water‐based surfactant‐free technology. The synthesis and properties of uniform silica‐coated hematite particles with adjustable size, morphology, and silica shell thickness are discussed in detail. The developed method allows simultaneous formation of the silica shell around hematite core and incorporation of reactive groups on the surface of core–shell nanoparticles. Vinyl groups are introduced to the silica surface at once by pre‐functionalization of a water‐soluble hyperbranched polyalkoxysiloxanes with active double bonds. The reactivity of these surface‐immobilized vinyl groups is demonstrated by covalent attachment of rhodamine B using a thiol‐en click reaction.